Reviving Islamic Religious Education: A Transformative Journey in Banten's High Schools - Ali Nurdin; Samudi Samudi (STAI Hubbulwathan Duri, 2023)
Given the persisting issues among high school students in Banten about their inadequate comprehension of Islamic religious education content, particularly in relation to corpse management, it is imperative to revise and enhance the Islamic religious education curriculum in these schools. The objective of this study is to investigate and assess the changes, approaches, and assessment of Islamic religious education instruction in high schools in Banten. The research findings indicate that Islamic religious education material in Senior High Schools can be renewed by incorporating corpse management material and guide tutorial modules. This renewal can also involve adopting the Blended Learning method, which combines traditional teaching methods with online resources such as package books, assignments, and tutorials accessed through e-learning platforms like 'Sipintar', Quizzizz, and Google Classroom. Additionally, the evaluation of Islamic religious education in high schools can be enhanced by implementing evaluation instruments that focus on online corpse management material. These evaluations can be conducted using the 'Sipintar', Quizzizz, and Google Classroom applications.